INTERNATIONAL LEGAL REGULATION OF SPACE AND HIGH SEAS - ASPECTS OF HUMANKIND LEGAL PERSONALITY - Savic, Matej (Politeia, 2023)
In this paper, the author analyzes open issues regarding the status of humankind in International Law, pointing out particular problems related to its international legal personality, primarily from the angle of the Law of the Sea and the Cosmic Law. A special place in this paper is dedicated to international regulations in the field of the Law of the Sea and Cosmic Law in which there is no possibility of establishing sovereignty, where states, as basic subjects of International Law, do not have exclusive competencies. The idea of humankind as a subject of International Law is primarily viewed from the angle of particular areas of International Law in which states are not exclusive holders of rights and duties. Humankind is analyzed as a specific and, above all, abstract concept in International Law